Optimal Cover Prices and the Effects of Website Provision on Advertising and Magazine Demand - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
I derive and estimate a model for cover price setting in print media markets where actors are faced by two interrelated demand curves: the demand for the print medium and the demand for advertising space. Publicly available data on German women?s magazines observed between 1998 and 2001 are used in the GMM estimation. Main findings are that my estimated marginals cost coincide well with those of industry sources, magazines with a high circulation elasticity of advertising demand price markedly below marginal cost and website provision neither has a significant effect on magazine nor on advertising demand. Keywords: magazines, cost estimation, GMM estimation, website provision
Keywords: L11; C33; 330; magazines; cost estimation; GMM estimation; website provision; Zeitschrift; Betriebliche Preispolitik; Homepage; Zeitungswerbung; Nachfrage; Frauen; Spezialzeitschrift; Internet; Produktdifferenzierung; Schätzung; Deutschland